Age stereotyping of gay and heterosexual men: Why does a minority sexual orientation blur the age of old men, in particular?. (28th April 2022) - Coladonato, Rosandra; Bianchi, Mauro; Case, Federica; Carnaghi, Andrea
Abstract: This research examined age stereotyping of male individuals displaying intersectional memberships stemming from the combination of age (Young vs. Elderly) and sexual orientation categories (Gay vs. Heterosexual). We found that the age stereotypes of 'Elderly gay men' were blurred: 'Elderly gay men' were stereotyped less on elderly‐ and more on young‐stereotypical traits than both 'Elderly heterosexual men' (Study 1) and 'Elderly men' (Studies 2–4). These findings did not occur with any subtype, as was also not the case for 'Elderly right‐handed men' (Study 3), but replicate only with atypical subtypes (Study 4). Indeed, the blurring of the age stereotypes for 'Elderly gay men' was replicated for an additional atypical subtype, 'Elderly Atheist men', and amplified when the atypical subtype involved 'Elderly men' in combination with 'Athlete men', whose stereotypes implied youthful traits (Study 4). The results informed cognitive models of multiple category stereotyping.